Intelligent Systems for Computer Modelling Proceedings of the 1st European-Middle Asian Conference on Computer Modelling 2015, EMACOM 2015 - Styskala, Vitezslav; Kolosov, Dmitrii; Snasel, Vaclav; Karakeyev, Taalaybek; Abraham, Ajith; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume of Advances in Intelligent Systems and Computing contains papers presented at the 1st European-Middle Asian Conference on Computer Modelling, EMACOM 2015. This international conference was conceived as a brand new scientific and social event of mutual collaboration between the VSB - Technical University of Ostrava (Ostrava, Czech Republic) and the Kyrgyz National University named after J. Balasagyn (Bishkek, Kyrgyz Republic). The aim of EMACOM 2015 was to present the latest development in the field of computer-aided modelling as an essential aspect of research and development of innovative systems and their applications. The conference showed that together with simulations, various modeling techniques, enabled and encouraged by the rapid development of high-performance computing platforms, are crucial for cost-efficient design, verification, and prototyping of solutions in many diverse industrial fields spanning the whole range from manufacturing, mining, machinery, and automotive industries to infrastructure planning and development, economics, energy, and modern agriculture and food industry.
Finite Element Modelling of T-Plate for Treatment of Distal Radius -- The Enlarged D-Q Model of Induction Motor with the Iron Loss and Saturation Effect of Magnetizing and Leakage Inductance -- Fuzzy Model Based Intelligent Prediction of Objective Events -- Using Multiple Scanning Devices for 3-D Modeling -- More Effective Control of Linear Switched-Reluctance Motor Based on the Research of Electromagnetic Processes of Field Theory Methods Linear Electrical Machines -- Numerical Simulation of the Structural Elements of a Mobile Micro-Hydroelectric Power Plant of Derivative Type -- Complex System Modeling with General Dierential Equations Solved by Means of Polynomial Networks -- Monte Carlo Probabilistic Approach Applied for Solving Problems in Mining Engineering -- Investment Funds Management Strategy Based on Polynomial Regression in Machine Learning -- Detecting Hidden Patterns in European Song Contest - Eurovision 2014 -- Numerical Solution of Volterra Linear Integral Equation of the Third Kind -- Cluster Analysis of Data with Reduced Dimensionality: an Empirical Study -- Comparison of Energy Near-Optimal Control Laws for the Drives with Constant and Linear Frictions -- Systems of Temporal Logic for a Use of Engineering. Toward a More Practical Approach -- Software Determining Optimum Order for Maintenance -- Statistical Evaluation of Dimmable Interior Lighting System Consumption Using Daylight -- User Identication by Biometric Methods -- Energy Modelling of the Building -- Reconstruction of 4D CTA Brain Perfusion Images Using Transformation Methods -- Segmentation of Macular Lesions Using Active Shape Contour Method -- Mathematical and Experimental Analyses of a Compression Ignition (CI) Engine Run on a Bioethanol Diesel Emulsion -- Modelling of Antiphase Noise Reduction of a Transformer.
Keywords: Computational intelligence; Artificial intelligence; Computer simulation; Computational Intelligence; Artificial Intelligence; Computer Modelling